1965
DOI: 10.1530/jrf.0.0100085
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Induction of Pseudopregnancy in Rats

Abstract: Various hormonal methods are compared of obtaining pseudopregnant rats capable of implanting fertilized ova transferred to them. Injection of 20 \g=m\g of oestrone to rats on Day 1 of pregnancy, followed by injection of 1 mg/day of medroxyprogesterone on Days 2 to 4, resulted in a high rate of implantation of fertilized ova transferred on Day 5. Non-pregnant rats were able to implant ova transferred to them when injected with prolactin, but not with progesterone. Indirect evidence is presented which indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1967
1967
1986
1986

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Carlson & DeFeo (1965) showed that implantation may be induced in rats with severed pelvic nerves by an injection of reserpine. Banik & Ketchel (1965) and Mantalenakis & Ketchel (19666) have shown that implantation of transferred blastocysts occurs in rats in which pseudopregnancy was induced by daily injection of prolactin. It seems that prolactin can suppress the formation and release of follicle-stimulating hormone and luteinizing hormone as suggested by Rothchild (1960), but since the implantation of transferred blastocysts occurs promptly after the removal of the suckling young in post-partum pseudopregnant rats, there appears to be a release of gonadotrophin in response to the withdrawal of the litter.…”
Section: Discussionmentioning
confidence: 99%
“…Carlson & DeFeo (1965) showed that implantation may be induced in rats with severed pelvic nerves by an injection of reserpine. Banik & Ketchel (1965) and Mantalenakis & Ketchel (19666) have shown that implantation of transferred blastocysts occurs in rats in which pseudopregnancy was induced by daily injection of prolactin. It seems that prolactin can suppress the formation and release of follicle-stimulating hormone and luteinizing hormone as suggested by Rothchild (1960), but since the implantation of transferred blastocysts occurs promptly after the removal of the suckling young in post-partum pseudopregnant rats, there appears to be a release of gonadotrophin in response to the withdrawal of the litter.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of 'pseudopregnancy' used here is a persistence of such a smear for 9 or more days followed bya return to oestrus, and the resumption of regular cycles. Quotation marks are used because of the doubt that this period is truly equivalent to the state of pseudo-pregnancy induced by sterile coitus or mechanical stimulation of the uterine cervix, in terms of the ability of the uterus to form deciduomata or permit implantation of blastocysts (Banik & Ketchel, 1965).…”
Section: Methodsmentioning
confidence: 99%
“…Such a deteriorated CAR performance was also observed in pseu dopregnancy (PSP), which is a condition normally induced by the agency of reproductive hormones [Banik and Ketchel, 1965;Rothchild and Schubert, 1963]. Hence, it is tempting to assume that the sex hormones, particularly progesterone, could be involved in this attenuation of emotionality that possibly accounted for the sub sequent behavioural effects in both normal pregnancy and PSP.…”
Section: Discussionmentioning
confidence: 99%